2018
DOI: 10.1177/0886260518786495
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Low Self-Control and Delinquent Peer Associations on Bullying Growth Trajectories Among Korean Youth: A Latent Growth Mixture Modeling Approach

Abstract: The emergence of studies applying Gottfredson and Hirschi's (1990) self-control theory to offending behaviors has produced empirical support confirming the position that individuals with low self-control are more likely to engage in deviant behaviors. However, few have examined its effects with opportunity factors. The present study examines the time-invariant effect of low self-control, as well as the time-concurrent and lagged effects of opportunity factors (parental attachment and delinquent peer associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Various longitudinal studies analyzing bullying (Barker et al, 2008; Cho & Lee, 2018; Pepler et al, 2008) have adopted growth mixture modeling or related semiparametric group-based modeling approaches to better understand the distinct patterns in bullying (i.e., heterogeneity), its developmental origins and correlates, and its growth over time (Cho & Lee, 2018). These studies found support for three to five distinct developmental trajectories of involvement in bullying and victimization across time, including a low/stable trajectory group, a high/chronic trajectory group, and other groups that exhibit increased or decreased involvement over time (Barker et al, 2008; Cho & Lee, 2018; Goldbaum et al, 2003; Reijntjes et al, 2013). Studies using growth trajectory analyses tend to focus on developmental (e.g., child’s behavior, social cognitions, and social problem-solving skills) and contextual factors (e.g., relationships with parents and peer groups) (Pepler, 2006; Pepler et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Various longitudinal studies analyzing bullying (Barker et al, 2008; Cho & Lee, 2018; Pepler et al, 2008) have adopted growth mixture modeling or related semiparametric group-based modeling approaches to better understand the distinct patterns in bullying (i.e., heterogeneity), its developmental origins and correlates, and its growth over time (Cho & Lee, 2018). These studies found support for three to five distinct developmental trajectories of involvement in bullying and victimization across time, including a low/stable trajectory group, a high/chronic trajectory group, and other groups that exhibit increased or decreased involvement over time (Barker et al, 2008; Cho & Lee, 2018; Goldbaum et al, 2003; Reijntjes et al, 2013). Studies using growth trajectory analyses tend to focus on developmental (e.g., child’s behavior, social cognitions, and social problem-solving skills) and contextual factors (e.g., relationships with parents and peer groups) (Pepler, 2006; Pepler et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Jenkins and colleagues (2016) found significant associations with bullying victimization and lower social skills, while other studies examining the psychological stability of youth found that bullying victims exhibited higher degrees of emotional problems (e.g., depression, anxiety, loneliness, and low self-esteem) (Jenkins et al, 2017; Nakamoto & Schwartz, 2010). To grasp the nature of bullying, a comprehensive understanding of its etiology is needed (Cho & Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations